Integrasi Nilai-Nilai Jurnalistik Profetik dalam Pengembangan Kompetensi Digital Marketing pada Era Transformasi Media Digital - Nur Ahmad, Fitria; Saragih, M. Yoserizal (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze the integration of prophetic journalism values into the development of digital marketing competencies in the era of digital media transformation and to formulate a value-based competency model. Employing a qualitative phenomenological approach, the study collected data through in-depth interviews with seven informants consisting of Islamic communication scholars, digital marketing practitioners, and senior undergraduate students. The data were analyzed using thematic analysis to identify patterns of understanding and implementation of prophetic values in digital marketing practices. The findings reveal that the values of humanization, liberation, and transcendence can be effectively integrated into digital communication strategies, content production, and audience relationship management. The implementation of these values contributes to enhancing credibility, integrity, ethical responsibility, and professional sustainability among digital marketing practitioners. The novelty of this study lies in the formulation of the Prophetic Digital Marketing Competence (PDMC) model, which integrates digital marketing competencies with prophetic journalism values as an ethical foundation for digital communication practices. The study concludes that prophetic values remain highly relevant as a moral framework for developing digital marketing competencies in the contemporary digital media landscape.